Stem Cell Research and Clinical Translation: A Roadmap about Good Clinical Practice and Patient Care - Paola Frati; Matteo Scopetti; Alessandro Santurro; Vittorio Gatto; Vittorio Fineschi (Stem Cells International)
The latest research achievements in the field of stem cells led in 2016 to the publication of “Guidelines for Stem Cell Research and Clinical Translation” by the International Society for Stem Cell Research (ISSCR). Updating the topics covered in previous publications, the new recommendations offer interesting ethical and scientific insights. Under the common principles of research integrity, protection of patient’s welfare, respect for the research subjects, transparency and social justice, the centrality of good clinical practice, and informed consent in research and translational medicine is supported. The guidelines implement the abovementioned publications, requiring rigor in all areas of research, promoting the validity of the scientific activity results and emphasizing the need for an accurate and efficient public communication. This paper aims to analyze the aforementioned guidelines in order to provide a valid interpretive tool for experts. In particular, a research activity focused on the bioethical, scientific, and social implications of the new recommendations is carried out in order to provide food for thought. Finally, as an emerging issue of potential impact of current guidelines, an overview on implications of compensation for egg donation is offered.